K-Means Clustering Symptoms of Covid-19 Positive in Indonesia - Wahyuddin S; Mahir Pradana (Jurnal Mantik, 2021)
This study aims to group the positive symptoms of covid-19 in Indonesia based on coronavirus symptom data. Some symptoms are characteristic of a person contracting positive coronavirus, usually causing respiratory infections, ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Like other respiratory diseases, COVID-19 can cause mild symptoms including colds, sore throats, coughs, and fevers. There are 14 main symptoms obtained from Indonesia's COVID-19 detention task force. The data was taken in August 2021. For grouping cases, this study used the K-Means Clustering method by using R studio software to analyze the data. After grouping, there are 3 groups of positive symptoms of covid-19 in Indonesia. Positive symptom grouping results are expected to provide feedback to policymakers to see which symptom groups need to take precedence.